Philosophy of Education In Digital Transformation: Ethical Considerations For Students’ Data Security In Online Learning Platforms - Ahmad Nusi; M Zaim (Jurnal Ilmiah Pendidikan Scholastic, 2023)
The integration of technology into education has ushered in transformative changes, but ethical considerations pose significant challenges. This survey-based study delves into the complexities of educational technology ethics, exploring perspectives from both lecturers and students in the context of Indonesian Society and Arts at Ekasakti University of Padang. Twenty students and three lecturers participated as respondents, shedding light on the ethical dimensions of technology integration. Lecturers exhibited diverse preferences in online learning platforms, emphasizing the need for flexibility in educational tools. Meanwhile, students generally expressed confidence in data security on e-learning platforms, coupled with a moderate awareness of privacy policies. However, experiences with security issues warrant attention, signaling areas for improvement in data protection measures. The study underscores the importance of understanding varied preferences among educators and enhancing data security measures to foster a positive online learning experience. By addressing ethical concerns, this research contributes to navigating the evolving landscape of educational technology, ensuring that the digital transformation aligns with ethical principles and facilitates meaningful learning experiences.